2019
DOI: 10.1111/ffe.13084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the stress state on plastic deformation and ductile failure: Experiment and numerical simulation using a newly designed tension‐shear specimen

Abstract: The stress state is one of the most notable factors that dominates the initiation of ductile fracture. To examine the effects of the stress state on plasticity and ductile failure, a new tension‐shear specimen that can cover a wide range of stress triaxialities was designed. A fracture locus was constructed in the space of ductility and stress triaxiality for two typical steels based on a series of tests. It is observed that the equivalent plastic strain at failure exhibits a nonmonotonic variation with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…FE calculations of the smooth and notched tensile specimens (R = 3 mm), shown in Figure 16A,B, respectively, proved their calculation are almost independent of the mesh sizes. Similar results were also found in previous studies, 6,55 which manifested the GTN model does not exhibit obvious mesh size dependency for un-cracked bodies. Therefore, except for f F , the determination of GTN parameters is independent of the mesh sizes.…”
Section: Discussionsupporting
confidence: 91%
“…FE calculations of the smooth and notched tensile specimens (R = 3 mm), shown in Figure 16A,B, respectively, proved their calculation are almost independent of the mesh sizes. Similar results were also found in previous studies, 6,55 which manifested the GTN model does not exhibit obvious mesh size dependency for un-cracked bodies. Therefore, except for f F , the determination of GTN parameters is independent of the mesh sizes.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, neither the initial value nor the final value of W f can be representative. In the process of determining the value of W f, in order to consider the impact of the loading history, it is reasonable to use the average value of stress triaxiality, of which the range can be obtain from an FE calculation, as described in the literature 20,31 :…”
Section: Calibration Of Materials Parameters In the Mfse Modelmentioning
confidence: 99%
“…Moreover, Kim's group successfully applied this simple model to reproduce the crack growth behaviours of C(T) specimens, 15 cracked plates 16 and cracked pipes, 15 and recently proposed a stress-modified multiaxial fracture strain energy (MFSE) model, [17][18][19] which will be introduced later in Section 3.1. Most recently, a tension-shear specimen that can cover a wide range of values of the stress triaxiality was designed by Zhang et al 20 It has been demonstrated that, for stainless steel, 316 L, and low-carbon steel, SM400A, the fracture strain does not necessarily decrease monotonically as the stress triaxiality increases. Unlike the VGM and SMCS model, the GTN model [7][8][9] explicitly considers the voids and is one of the best known models for describing the ductile failure of metals.…”
Section: Introductionmentioning
confidence: 99%
“…Although a lot of effort is being spent on investigating the influence of Lode parameter on the damage and fracture behavior of metallic materials, 15,[34][35][36][37][38][39][40][41] the effects of Lode parameter on damage and fracture behavior for polymeric materials have yet to be fully understood due to the different deformation mechanisms involved in the plasticity of metallic and polymeric materials. Scarcity of information in this area provides motivation for the current study.…”
Section: Introductionmentioning
confidence: 99%